خَصَائِصُ الُلغَةِ الْعَرَبِيَّةِ الْفُصْحَى وَمَكَانَتُهَا فِيْ الدِّيْنِ الْإِسْلَامِيْ - Asni Furoidah (Al-Fusha : Arabic Language Education Journal, 2019)
Arabic is the best language and its name. It has characteristics that distinguish it from other language. The Arabic language has unique features and characteristics that are unique to other languages ​​in the historical, religious and cultural aspects, as well as the linguistic aspects of sounds, morphology, grammar, significance and rhetoric. Historically speaking, Arabic is one of the oldest and most ancient languages. It is the mother of the oldest languages. Religiously and culturally, Arabic is a sacred language in the heavenly religions that preceded Islam. Linguistic features such as phonetic, morphological, grammatical, lexical and semantic characteristics are many linguistic features. Classical Arabic has been distinguished from the language generated by expression. Classical Arabic becomes the language of literature and culture. Classical Arabic is the language of the Holy Qur›an that was revealed to our Prophet Muhammad (peace be upon him) and blessings and peace of Huda for the people. Arabic is the means of preserving the ideological and cultural heritage of the Arab Islamic nation.